Memes go beyond humor: a multimodal reading for construction of meaning - Guerreiro, Anderson (2016)
The advent of new digital media has brought to the cybernetic environment innovative ways of communicating and using the language, making it more dynamic and visual. In parallel to this, new genres arise as a result of changes in cyberspace. Meme is one of these and stands out for its accentuated presence on social networks. Assessing its importance in the current context, we seek to analyze the discursive visual configuration present in this digital genre. We took as object of analysis two memes, chosen because they have been widespread on social networks and for conducting social practices about contemporary life. The analytical categories used are those of the Theory of Multimodal Social Semiotics (TMSS): The assumptions of Kress, Leite-Garcia and van Leeuwen (2002) regarding the semiotic conception of the multimodal texts in their external aspects were adopted, considering the moment of production, an influence of the reader, a culture and the social context; As well as the Grammar of Visual Design (GVD), theory developed by Kress and Leeuwen (2006), that analyzes the representational, interactive and compositional meanings, concerning the construction of sense, both humorous and critical, considering the participants presented in the images, the interaction with the observer and the image composition. The analysis demonstrated that these genres are widespread in social networks, serving both for the dissemination of everyday topics and for specific criticism about situations experienced by many people.